Respuestas

2013-09-19T07:48:02+02:00
Ley de radicación para los casos 1, 2 y 3  

 \sqrt[n]{x}  \sqrt[m]{x} = x^{ \frac{1}{n} + { \frac{1}{m} }  } = x^{ \frac{n+m}{nm} } = \sqrt[nm]{ x^{n+m} }

 \sqrt{a}  \sqrt[3]{x} = \sqrt[3]{ a^{4} }

 \sqrt[3]{2} \sqrt[4]{2} =  \sqrt[12]{ 2^{7} }

 \sqrt{5} \sqrt[4]{5} } =  \sqrt[4]{ 5^{5} }

Ley de radicación para los casos 4 y 5:

 \frac{ \sqrt[n]{a} }{ \sqrt[n]{b} } =  \sqrt[n]{ \frac{a}{b} }

 \frac{ \sqrt{6} }{ \sqrt{3} } =  \sqrt{ \frac{6}{3} } = \sqrt{2}

 \frac{ \sqrt[3]{30} }{ \sqrt[3]{5} } = \sqrt[3]{ \frac{30}{5} } = \sqrt[3]{6}


LISTO!!!